All-in-one mobile halal restaurant application / Abdul Razak Mohd Khir - Mohd Khir, Abdul Razak (2017)
Evolvement of digital application has changed from desktop to mobile. The necessity of mobile app is crucial in providing information and also in locating places. This case also applied to Muslim tourist in their finding for Halal food. To find it, it is not suitable if they search via web page or social media as it turns out to be waste of time. To cater this problem, the need of all-in-one Halal mobile app is developed. Five features are centred in this project are business information, location, review rating and add restaurant. This project used Mongo Atlas and the data is stored in MongoDB database. Scripting language is used to invoke these data and using AJAX to send the data to JavaScript before display it using Web Development Language. The data received from the database is in JSON format and translated into JavaScript object to enable viewing properties. There is a testing phase done by a group of user to test the effectiveness of the features. The findings are then accumulated and recorded. Hence, this mobile hybrid application is being developed throughout this project and tested in Android version 4.1.2 with integration of PhoneGap framework.